Depression symptoms as mediators of inequalities in self-reported health - Leão, T (2018)
Background: Inequalities in the distribution of self-reported health (SRH) have been widely reported. Its higher expressivity among women, elderly and least educated groups has been partly attributed to differences in their health perceptions. However, this subjectivity may be masking the burden of mental illness in these groups. Thus, we sought to understand if depression symptoms mediate inequalities in SRH. Methods: SHARE waves 4 and 6, pertaining to Spain, Italy and Portugal, were used (n2011 = 8517, n2015 = 11 046). Inequalities in SRH were calculated, comparing the risk amongst education level, gender and age groups, adjusting for chronic diseases, functional limitations and country fixed effects. We then tested depression symptoms as mediators. Results: Depression symptoms were associated with poor SRH (odds ratio (OR)2011 = 1.379, OR2015 = 1.384, P < 0.001). Their inclusion reduced the magnitude of the association between SRH and education, annulled the statistical significance for age, and reversed the gender effect. As expected, chronic diseases and functional limitations remained significant predictors of poor SRH. Conclusions: Depression symptoms, together with chronic diseases and functional limitations, explain the poorer SRH of the least educated, female and older groups in the Southern European population. Therefore, tackling inequalities in SRH must require focusing on mental health issues, which disproportionately affect the most vulnerable groups.